2018
DOI: 10.1186/s41182-018-0126-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated risk factors of Strongyloides stercoralis infection in Lower Myanmar

Abstract: BackgroundStrongyloidiasis is prevalent in Southeast Asian regions along with other soil-transmitted helminthiases, but only limited present-day data was available for Myanmar.MethodsA prevalence survey for Strongyloides stercoralis infection was conducted among villagers in rural areas of three townships located in the Lower Myanmar during 2014–2016 by agar plate culture method in combination with specific identification by molecular assays. Risk factors associated with S. stercoralis infection were assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…In neighbouring Southeast Asian countries, higher prevalence rates of S. stercoralis infection have been reported in Cambodia (Forrer et al ., 2018), Lao PDR (Vonghachack et al ., 2015) and Thailand (Laoraksawong et al ., 2018), while much lower prevalence rates were reported in Indonesia (Wiria et al ., 2013) and Myanmar (Aung et al ., 2018). Nevertheless, it is believed that strongyloidiasis is likely to have a much higher burden in Southeast Asia than currently indicated in the available literature (Schär et al ., 2016) not least because the region exhibits conditions that favour high transmission of strongyloidiasis, such as humid and wet climates, inadequate sanitary conditions and poverty (Al-Mekhlafi et al ., 2013; Schär et al ., 2013).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In neighbouring Southeast Asian countries, higher prevalence rates of S. stercoralis infection have been reported in Cambodia (Forrer et al ., 2018), Lao PDR (Vonghachack et al ., 2015) and Thailand (Laoraksawong et al ., 2018), while much lower prevalence rates were reported in Indonesia (Wiria et al ., 2013) and Myanmar (Aung et al ., 2018). Nevertheless, it is believed that strongyloidiasis is likely to have a much higher burden in Southeast Asia than currently indicated in the available literature (Schär et al ., 2016) not least because the region exhibits conditions that favour high transmission of strongyloidiasis, such as humid and wet climates, inadequate sanitary conditions and poverty (Al-Mekhlafi et al ., 2013; Schär et al ., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the APC method showed superior sensitivity (174 cases) in detecting S. stercoralis larvae in fecal samples compared to direct smear (two cases), FES (15 cases) and conventional PCR (157 cases), with six samples found positive only by PCR. These results are consistent with those reported elsewhere (Requena-Méndez et al ., 2013; Amor et al ., 2016; Aung et al ., 2018; Tuyizere et al ., 2018). It is also interesting to note that the number of positive cases detected by the combined methods was not significantly different from using APC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations